2023
DOI: 10.1002/ecy.3944
|View full text |Cite
|
Sign up to set email alerts
|

Spatial scale‐dependent dilution effects of biodiversity on plant diseases in grasslands

Abstract: The rapid biodiversity losses of the Anthropocene have motivated ecologists to understand how biodiversity affects infectious diseases. Spatial scale is thought to moderate negative biodiversity-disease relationships (i.e., dilution effects) in zoonotic diseases, whereas evidence from plant communities for an effect of scale remains limited, especially at local scales where the mechanisms (e.g., encounter reduction) underlying dilution effects actually work.Here, we tested how spatial scale affects the directi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…Migration of ephemeral-specialised nematodes provides a spatial factor in the host-parasite dynamics that might be compared to that of a fragmented landscape. A systematic experiment altering host diversity of plant patches indicated dilution effects of a fungal disease became stronger on smaller spatial scale (Liu et al 2023). This confirmed an earlier correlation study that demonstrated biotic interactions have more profound effects on prevalence of amphibian chytrid fungus, West-Nile virus and Borrelia burgdorferi (causing Lyme's disease) on a local than continent-wide scale (Cohen et al 2016).…”
Section: Potential Mechanistic Bases Of Dilution Effects In Ephemeral...supporting
confidence: 80%
See 2 more Smart Citations
“…Migration of ephemeral-specialised nematodes provides a spatial factor in the host-parasite dynamics that might be compared to that of a fragmented landscape. A systematic experiment altering host diversity of plant patches indicated dilution effects of a fungal disease became stronger on smaller spatial scale (Liu et al 2023). This confirmed an earlier correlation study that demonstrated biotic interactions have more profound effects on prevalence of amphibian chytrid fungus, West-Nile virus and Borrelia burgdorferi (causing Lyme's disease) on a local than continent-wide scale (Cohen et al 2016).…”
Section: Potential Mechanistic Bases Of Dilution Effects In Ephemeral...supporting
confidence: 80%
“…Moreover, migration of ephemeral-specialised nematodes provides a spatial factor in the host-parasite dynamics that might be compared to that of a fragmented landscape. Fragmentation of ephemeral nematode communities may further contribute to the observation of diversity-disease effects [15,20,70,71].…”
Section: Potential Mechanistic Bases Of Diversity-disease Effects In ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Different effects may also occur at the individual plant and species scale, depending on the consumer group. Fungal pathogens may respond more strongly to small scale (a few 10cms) variation in neighbourhood properties (Barbosa et al 2009;Liu et al 2023), meaning that effects of the surrounding neighbourhood may be stronger for individual plants than for species in larger patches. Most insect herbivores actively search for their host plants and may respond to variation in plant neighbourhoods only at larger scales.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, insect herbivores may also be able to better select their host plants, leading to more variation in insect herbivore attack between plant individuals and species in a community, which might make it harder to scale effects from individuals to species and communities. Some studies have looked at different effects of consumers at different spatial scales (e.g., Liu et al 2023) but few have compared effects between organisational levels.…”
Section: Introductionmentioning
confidence: 99%